333 THE LONG-TERM TREATMENT OUTCOMES OF ESOPHAGEAL SCC WITH MM/SM1 INVASION AFTER ENDOSCOPIC RESECTION. (17th September 2021) - Naito, Sakiko; Yoshio, Toshiyuki; Yoshimizu, Shoichi; Ishiyama, Akiyoshi; Tsuchida, Tomohiro; Itoi, Takao; Fujisaki, Junko
Abstract: : Resent advances in endoscopic resection (ER) provide us increasing chances for resecting esophageal SCC with muscularis mucosae (MM) and submucosal (SM) invasion. We perform additional therapy such as chemoradiotherapy (CRT) or esophagectomy considering the risk of metastasis and patient's condition. However, there is only a few reports about long-term outcome after ER for such cases. Methods: We retrospectively studied 188 case of esophageal SCC with pathological MM invasion resected by ER (161 cases) and SM1(27 cases) from 2005 to 2016 in Cancer Institute Hospital. We recommended CRT or esophagectomy as additional treatment for the cases which had lymphovascular invasion (LVI) or DI (droplet infiltration) considering patients' conditions. Median observation period of them were 71 months. Results: The SM1 cases had significantly higher rate of LVI than the MM cases. Of 161 MM cases, 2 cases had recurrence, however, they are alive after CRT or CRT following esophagectomy. Of 27 SM1 cases, 3 cases had LN recurrence, underwent RT or CRT or CRT following esophagectomy, one case died of esophageal SCC and the others survive. The rate of metastatic cases was higher in SM1 than that in MM. Overall survival rate in 5 years were 89.8% in MM and 81.8% in SM1. Cause specific survival rate in 5 years were 100% in both MM and SM1. Conclusion: The long-term outcomes of ER for MM/SM1 invasive esophageal SCC was good with appropriate additional therapy which we should perform in high risk cases for LN metastasis considering patients' condition.